نمذجة التدفقات الشهرية لنبع السن في الساحل السوري باستخدام تحليل السلاسل الزمنية - حايك, شريف; حماد, منذر (Latakia University Journal -Engineering Sciences Series, 2018)
تعتمد دراسة وتصميم المآخذ المائية للينابيع على تحليل السلاسل الزمنية للقياسات التاريخية من خلال التنبؤ بأحجام المياه الواردة أو المتوقع ورودها مستقبلاً. يهدف البحث إلى نمذجة تدفقات المياه الشهرية لنبع السن في الساحل السوري والتنبؤ المستقبلي بهذه التدفقات، باعتماد نماذج "بوكس– جنكنز" في تحليل بيانات السلسلة الزمنية، لارتفاع درجة الدقة في تنبؤاتها. اعتمدنا بيانات تدفقات المياه الشهرية وبالتالي حجوم المياه الشهرية لـ 101 شهراً من حزيران 2008 حتى تشرين الأول 2016م، وبعد إجراء عمليات استقرار السلسلة في التباين والمتوسط وإزالة الموسمية وتنفيذ الاختبارات المطلوبة على بواقي النموذج، تبيّن أن أفضل نموذج يمثل البيانات هو SARIMA(2,0,1) (2,1,0)12، وتم تقسيم البيانات إلى 81 شهراً لبناء النموذج و20 شهراً لاختباره، واعتماداً على أصغر قيمة للمتوسط الموزون للمعايير RMSE, MAP, MAE، فإن أفضل نموذج للتنبؤ هو النموذج SARIMA(3,1,0) (1,1,0)12، وقد أعطى النموذج تنبؤات قريبة من حجوم المياه الشهرية في النبع المقيسة فعلياً. The study and design of water-intakes on springs is based on the analysis of time series of historical measurements to achieve prediction of incoming water volumes or future expected. The research aims to model the monthly water flows of AL-SIN Spring in Syrian Coast and future expectations of these flows, by adopting the Box-Jenkins models to analyze the time series data, due to its reliable accuracy. Monthly water flows, thus, monthly volumes, for 101 month (from June 2008 to October 2016) were processed. Performing the stability of the time series on variance and median and non-seasonality and making the wanted tests on model residuals, we found that the best model to represent the data is SARIMA(2,0,1) (2,1,0)12 , and after dividing the data into 81 month to build the model and 20 month to test it. Depending on the smallest of weighted mean of criteria RMSE, MAP, MAE,. The best predicted model was SARIMA (3,1,0) (1,1,0)12 and the model gave the nearest predicted values to actually measured data in spring.